Limosilactobacillus urinaemulieris sp. nov. and Limosilactobacillus portuensis sp. nov. isolated from urine of healthy women. Issue 3 (1st March 2021) - Ksiezarek, Magdalena; Ribeiro, Teresa Gonçalves; Rocha, Joana; Grosso, Filipa; Perovic, Svetlana Ugarcina; Peixe, Luisa
Abstract : Two Gram-stain-positive strains, c9Ua_26_M T and c11Ua_112_M T, were isolated from voided urine samples from two healthy women. Comparative 16S rRNA gene sequences demonstrated that these novel strains were members of the genus Limosilactobacillus . Phylogenetic analysis based on pheS gene sequences and core genomes showed that each strain formed a separated branch and are closest to Limosilactobacillus vaginalis DSM 5837 T . The average nucleotide identity (ANI) and Genome-to-Genome Distance Calculator (GGDC) values between c9Ua_26_M T and the closest relative DSM 5837 T were 90.7 and 42.9 %, respectively. The ANI and GGDC values between c11Ua_112_M T and the closest relative DSM 5837 T were 91.2 and 45.0 %, and those among the strains were 92.9% and 51, 0 %, respectively. The major fatty acids were C12 : 0 (40.2 %), C16 : 0 (26.7 %) and C18 : 1 ω 9 c (17.7 %) for strain c9Ua_26_M T, and C18 : 1 ω 9 c (38.0 %), C16 : 0 (33.3 %) and C12 : 0 (17.6 %) for strain c11Ua_112_M T . The genomic DNA G+C content of strains c9Ua_26_M T and c11Ua_112_M T was 39.9 and 39.7 mol%, respectively. On the basis of the data presented here, strains c9Ua_26_M T and c11Ua_112_M T represent two novel species of the genus Limosilactobacillus, for which the names Limosilactobacillus urinaemulieris sp. nov. (c9Ua_26_M T =CECT 30144 T =LMG 31899 T ) and Limosilactobacillus portuensis sp. nov. (c11Ua_112_M T =CECT 30145 T =LMG 31898 T ) are proposed.